2016
DOI: 10.1152/japplphysiol.00432.2016
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial glucose concentrations and hypoglycemia during 2 days of caloric deficit and sustained exercise: a double-blind, placebo-controlled trial

Abstract: Military personnel and some athlete populations endure short-term energy deficits from reduced energy intake and/or increased energy expenditure (EE) that may degrade physical and cognitive performance due to severe hypoglycemia (<3.1 mmol/l). The extent to which energy deficits alter normoglycemia (3.9-7.8 mmol/l) in healthy individuals is not known, since prior studies measured glucose infrequently, not continuously. The purpose of this study was to characterize the glycemic response to acute, severe energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Indeed, we observed lower HT insulin concentrations in PSE when compared to MDX (Fig. 2 b) and fewer participants experienced hypoglycaemia (defined as glucose concentrations < 3.8 mmol l −1 ; Balijepalli et al 2017 ; Smith et al 2016 ) at 60 min (18 versus 27%). Moreover, the change in glycaemia from HT was also less in PSE compared to MDX (− 4%; − 0.2 ± 0.75 mmol l −1 versus − 19%; − 1.0 ± 1.31 mmol l −1 ; P = 0.015) at 60 min (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…Indeed, we observed lower HT insulin concentrations in PSE when compared to MDX (Fig. 2 b) and fewer participants experienced hypoglycaemia (defined as glucose concentrations < 3.8 mmol l −1 ; Balijepalli et al 2017 ; Smith et al 2016 ) at 60 min (18 versus 27%). Moreover, the change in glycaemia from HT was also less in PSE compared to MDX (− 4%; − 0.2 ± 0.75 mmol l −1 versus − 19%; − 1.0 ± 1.31 mmol l −1 ; P = 0.015) at 60 min (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…Considering that the locomotive muscle aerobic metabolism, as determined by the NIRS measures on the vastus lateralis, was not perturbed by SUSOPS, the greater pulmonary O 2 values were probably attributable to higher metabolic demands of other tissues; for instance, of the metabolic costs associated with the exaggerated exercise hyperpnoea and the hyperkinetic circulation in the SUSOPS trials. It is also plausible that, following SUSOPS, the amount of liver and skeletal muscle glycogen was relatively low, as suggested by the lower RER (i.e., enhanced rate of lipolysis) and capillary [La] (Smith et al 2016 ; Rognum et al 1981 ); a condition that may explain, at least partly (Bahr et al 1991 ), the increase in submaximal values of systemic O 2 , as well as of HR, E and RPE (Lima-Silva et al 2011 ; Carter et al 2004 ; Heigenhauser et al 1983 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, military-based studies have suggested that a prolonged period of sustained operations (SUSOPS) degrades cognitive and physical performance; thus, aerobic work capacity is typically suppressed (Guezennec et al 1994 ; Nindl et al 2002 ). Physiological and psychological modifications, such as low energy substrate availability (Smith et al 2016 ; Rognum et al 1981 ), muscle-mass loss (Johnson et al 1994 ), hypovolemia and/or hypohydration (Lieberman et al 2005 ; Wittels et al 1996 ), functional peripheral deteriorations (e.g., impaired mitochondrial efficiency; Fernstrom et al 2007 ), and decreased motivation and enhanced effort perception (Lucas et al 2009 ; Lieberman et al 2005 , 2006 ), have been regarded as potential determinants of physical performance in such multi-stressor conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It is understood that acute reductions in BG occur as a result of imbalances between EI and total energy expenditure and, thus, may be an important early warning sign that LEA is disturbing metabolic homeostasis (Koehler et al, 2016;Loucks, 2006;Loucks & Thuma, 2003). The effect of an acute (2 days), severe energy deficit (EI 270 kcal/day; total daily energy expenditure ∼4,000 kcal/day) on interstitial glucose responses using CGMs has been investigated in 23 healthy military personnel (Smith et al, 2016). Interstitial glucose concentrations were lower (4.1 ± 0.8 mmol•L −1 vs. 5.0 ± 1.2 mmol•L −1 ) and mean percentage of time in hypoglycemia (< 3.9 mmol•L −1 ) higher (38.7% ± 25.0% vs. 13.6% ± 13.7%) during severe energy deficit compared with energy balance, indicating perturbations to interstitial glucose control following a period of restricted EI coupled with increased exercise energy expenditure (Smith et al, 2016).…”
Section: Cgm and Leamentioning
confidence: 99%